Quizizz-online gamification on learning engagement and outcomes in English lecturing process - Rokhaniyah, Hesti; Ardiyanti, Dwi; Hidayat, Nurul (Institute of Advanced Engineering and Science, 2025)
Gamification entails incorporating elements of games into non-game settings with the goal of motivating learners to actively participate in learning. Much literature highlighted the potential of gamification in enhancing learning interest; however, very few researches delved gamification of Quizizz online for learning grammar. This research explored the effects of Quizizz on learning engagement and outcome while studying grammar. This study involved English lecturer and 68 learners in the second semester of a private university in Ponorogo, Indonesia. The data in this research was analyzed using a qualitative approach through classroom-based ethnography, including lecturer interviews, observations, and scrutiny of Quizizz test performances. The interpretation involved examining trends in learners' engagement and mean scores of Quizizz tests. The results of the research indicated that the competitive features in Quizizz such as rankings and limited time enhanced their engagement, marked by increased discipline and active involvement. Nevertheless, the fluctuation in learning outcomes was observed due to variations in topic difficulty, particularly evident with topic 1 (conjunction) being less challenging compared to the more difficult topics 2 (subject-verb agreement) and 3 (passive voice). Topic 2, characterized by its complexity, posed the greatest difficulty, emphasizing the importance of customizing quiz difficulty levels to optimize the effectiveness of Quizizz in the learning process.